Implications of the Growing Deployment of Electric Vehicles in Thailand and Strategic Adaptation of the Fuel Supply Chain - Nakapreecha, Nitida; Wangjiraniran, Weerin; Pongthanaisawan, Jakapong (International Journal of Energy Economics and Policy, 2026)
Thailand’s transition toward electric vehicles (EVs), driven by the national “30@30 policy,” is expected to significantly reduce oil consumption and reshape the country’s fuel supply chain. This study examines the impacts of EV adoption on refined petroleum demand and assesses adaptation strategies for key operators across the petroleum supply chain, including refineries, traders, ethanol and biodiesel producers, oil depots, and transport operators. Three energy scenarios—High Oil Demand, National Energy Plan, and Low Oil Demand—were analyzed using the LEAP model and transport-sector energy models to project future energy use and supply under varying levels of EV penetration. The findings indicate that refined petroleum demand will peak around 2028–2030 before declining, with the most substantial reductions occurring in gasoline and diesel consumption, while aviation fuel and LPG remain relatively stable. The study identifies three main adaptation approaches for industry operators: core business development, business integration, and business transformation. Policy recommendations emphasize maintaining consistent fuel policies, strengthening infrastructure systems such as pipelines and fuel depots, and supporting business diversification toward low-carbon energy. Together, these measures are essential to ensure a smooth, balanced, and resilient transition in Thailand’s energy and fuel sectors.